Pembingkaian Citra Polisi pada Tagar #PercumaLaporPolisi (Analisis Wacana Kritis Metode Norman Fairclough) - Yudha Ikhsan (UNIVED PRESS, Universitas Dehasen Bengkulu, 2022)
The purpose of this study is to examine the framing discourse used by digital activists in articulating their expectations regarding the services of the Indonesian National Police (Polri). All data is available through conversations that explore the narrative of Polri's services, including the associated hashtag, using the hashtag #PercumaLaporPolisi. The data was also thoroughly analyzed utilizing critical discourse analysis methodologies modified from Fairclough's (1995) paradigm, namely (1) description, (2) interpretation, and (3) explanation. Through the hashtag #PercumaLaporPolisi, the researchers were able to identify three framing strategies: (1) a delegitimization approach, (2) a frustration strategy, and (3) a comparison strategy. The study was successful in documenting the aims and hopes of digital activists who constantly interact in framing in Polri institutions.